A model of prehepatic portal hypertension in rats - Godik, Oleg; Zhumik, Dmytro; Diehtiarova, Daria; Levytskii, Anatolii; Lapikova-Bryhinska, Tetiana (The Ukrainian Scientific Medical Youth Journal, 2023)
during the study, the methodology of the prehepatic portal hypertension (PPH) develop- ment model in Wistar rats was set, using partial portal vein ligation (PPVL). It was followed by the anal- ysis of model stability and its prolongation over time using the indicator of the portal vein constriction rate (PVCR) and the portohepatic perfusion (PHP) dependence on it. It was found that in 4-week-old rats with a body weight of 99.6 ± 2.0 g there was no mortality in PPVL at 53.45%; the reduction of PHP was critical at 69.13% of PPVL; in a group of 6-week-old rats with a body weight of 155 ± 3.5 g, where the median PPVL was 58.67 (95% CI 56.3-59.82) after PPVL, there was no mortality. At the same time, a delay in the physical development of rats was noted in comparison with the control subgroup and the subgroup with false ligation. Parenchymal and vessel changes were registered on serial ultrasound examination.